2017
DOI: 10.3390/ijms18091999
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Monoclonal Antibodies Generated from Full Length Human Cereblon: Detection of Cereblon Protein in Patients with Multiple Myeloma

Abstract: Immunomodulatory drugs (IMiDs) are profoundly active compounds in the treatment of patients with multiple myeloma (MM). However, despite the fact that treatment with IMiDs has dramatically improved survival for patients with MM, the majority of MM patients develop IMiDs resistance over time. We have found that expression of functional cereblon is required for IMiDs′ action. In addition, it has been reported that cells expressing high levels of cereblon are resistant to proteasome inhibitor, implying that patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
2
1
Order By: Relevance
“…GSTP1 105 variant of this enzyme has less ability for detoxification, therefore the effectivity of cytostatic agents is increased in such multiple myeloma patients. In patients carrying the GSTP1 105Ile homozygous genotype, event-free and overall survival results were reported to be more favourable after alkylating agent or anthracyclin-based treatment [16]. In our cohort, neither GSTP1 105, nor GSTP1 114 polymorphisms had any impact on the treatment results and survival data.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…GSTP1 105 variant of this enzyme has less ability for detoxification, therefore the effectivity of cytostatic agents is increased in such multiple myeloma patients. In patients carrying the GSTP1 105Ile homozygous genotype, event-free and overall survival results were reported to be more favourable after alkylating agent or anthracyclin-based treatment [16]. In our cohort, neither GSTP1 105, nor GSTP1 114 polymorphisms had any impact on the treatment results and survival data.…”
Section: Discussioncontrasting
confidence: 59%
“…In patients having GSTP1 105 variant genotype, detoxification process was less active, therefore chemotherapeutical agents can be more effective. In MM patients carrying GSTP1 105Ile homozygous genes, progression-free (PFS) and overall survival results were reported to be more favourable [16].…”
Section: Introductionmentioning
confidence: 99%
“…Whether these associations may be driven by genetic variations in the CRBN gene remains unknown, as there are currently no clear biomarkers that predict response to lenalidomide therapy. Attempts to quantify cereblon’s utility as a clinical biomarker for IMiDs is ongoing 2023 . One study found an increased prevalence of mutations in both CRBN and the CRBN pathway impacting CRBN-IMiD interactions in patients with multidrug refractory disease, and subsequently observed conferred lenalidomide resistance in vitro following the functional introduction of these mutations in MM cells 24 .…”
Section: Introductionmentioning
confidence: 99%